Increasing the sensitivity of 2D high-resolution NMR methods applied to quadrupolar nuclei - Amoureux, J. P.; Delevoye, L.; Steuernagel, S.; Gan, Zhengting; Ganapathy, Subramanian; Montagne, L. (Journal of Magnetic Resonance, 2005)
Gan and Kwak recently proposed a soft-pulse added mixing (SPAM) idea in the classical two-pulse multiple-quantum magic-angle spinning scheme. In the SPAM method, a soft pi/2 pulse is added after the second hard-pulse (conversion pulse) and all coherence orders in between them are constructively used to obtain the signal. We, here, further extend this idea to distributed samples where the signal mainly results from echo pathways and that from anti-echo pathways dies Out after a few t(1) increments. We show that, with a combination of SPAM and collection of fewer anti-echoes, an enhancement of the signal to noise ratio by a factor of ca. 3 may be obtained over the z-filtered version. This may prove to be useful even for samples with long T'(2) relaxation times. (C) 2004 Elsevier Inc. All rights reserved.
Keywords: high-resolution; quadrupolar nuclei; sensitivity; Solid-state NMR